Comunidade e escola: reflexões sobre uma integração necessária - BEZERRA, Zedeki Fiel (2014)
This study presents reflections regarding the establishment of a partnership between the school and its community. With the objective of evaluating such partnership, researches were carried out in a public school and other in agreement, using questionnaires and interviews. The answers from the students and community members indicated different positions. For example: in the public school there were complains about the absence of interaction which led to a sensation of not belonging and indifference. On the other hand, in the university partnership school the community feels responsible for the school, thanks mainly to the possibilities of interaction that have been established. We have reached the conclusion that the community recognizes the importance of becoming involved in school actions, being school's responsibility to provide such access, by structuralizing an effectively significant teaching.